COST ANALYSIS OF SEAWATER DESALINATION USING AN INTEGRATED REVERSE OSMOSIS SYSTEM ON A CRUISE SHIP - Guler, E.; Engin, Onkal G.; Celen, M.; Erkan, Sari H. (Global Network Environmental Science & Technology, 2015)
The best method to treat seawater is known to be the use of reverse osmosis (RO) systems. The cost factor becomes the most important issue when using RO systems. Although quite costly, RO systems are essential systems for ships. As known very well, water is a critical resource on ships, especially the ones serving quite a large number of passengers. In this study, therefore, RO system capability under different conditions together with cost analysis was examined on a relatively small cruise ship. The system used had a daily water treatment capacity of 30 m(3). The RO system was composed of a sand filter, a cartridge filter, four pieces of membrane filter modules and a mineral filter. During the study, samples from the Black Sea, the Aegean Sea and the Mediterranean Sea, which have different physical and chemical properties, were examined from the quality point of view. A comprehensive cost analysis was also performed in order to determine the feasibility of the system for the production of potable water for a cruise ship.
Keywords: Reverse Osmosis; Seawater; Potable Water; Cost Analysis